Pharmacokinetics-based optimal dose prediction of donor source-dependent response to mycophenolate mofetil in unrelated hematopoietic cell transplantation - Wakahashi, Kanako; Yamamori, Motohiro; Minagawa, Kentaro; Ishii, Shinichi; Nishikawa, Shinichirou; Shimoyama, Manabu; Kawano, Hiroki; Kawano, Yuko; Kawamori, Yuriko; Sada, Akiko; Matsui, Toshimitsu; Katayama, Yoshio (International journal of hematology, 2011)
Mycophenolate mofetil (MMF) has been widely used for prophylaxis against graft-versus-host disease (GVHD) following allogeneic hematopoietic stem cell transplantation (allo-SCT). However, no clear advantage over methotrexate has been reported, other than reduced incidence of mucositis. We speculated that the wide inter-individual variation of plasma mycophenolic acid (MPA) levels veiled the benefits of MMF. Data from 36 unrelated allogeneic bone marrow (allo-BMT) and cord blood transplantation (CBT) were analyzed retrospectively based on MPA area under the curve (AUC 0–24h ). In allo-BMT, high AUC 0–24h (>30 μg h/ml) resulted in no incidence of grade II–IV acute/extensive chronic GVHD and tended to show higher overall and disease-free survival, lower relapse rates, and non-relapse mortality. In CBT, AUC 0–24h less than 30 μg h/ml was sufficient for low incidence of acute/chronic GVHD and high survival. Strong correlation between AUC 0–24h and C 2h , plasma MPA concentration at 2 h after administration was observed. Single point assessment of C 2h was shown to provide a useful surrogate of AUC 0–24h to predict GVHD incidence. The results of this study suggest that individualized MMF dosing in a donor source-dependent fashion may be important for maximizing the benefit of MMF in allo-SCT.